PENYULUHAN PENCEGAHAN DAN PENGENDALIAN PENYAKIT TIDAK MENULAR (PTM) UNTUK MENUMBUHKAN KESADARAN PENCEGAHAN PADA MASYARAKAT GANDOK, CONDONCATUR, SLEMAN, YOGYAKARTA - Anas Rahmad Hidayat; wahyu Joko Pamungkas (Permata Indonesia, 2022)
Non-communicable diseases (NCDs) are chronic diseases that cannot be passed from personto person. Deaths from NCDs are expected to continue to increase worldwide, the greatestincrease will occur in middle and poor countries. Non-communicable diseases (NCDs) are alsodiseases that are not transmitted and are not transmitted to other people by any form ofcontact, causing death and killing around 35 million people every year. Method: The approachused is counseling, because the community is easier to accept what is conveyed than what issought. Socialization is an easy and effective way of delivering messages. The purpose ofcommunity service is to detect risk factors for non-communicable diseases, in the Gandokcommunity, Condongcatur, Depok, Sleman, Yogyakarta. Types of activities carried out are inthe form of health education, therefore socialization and education are very important regardingthe Prevention and Control of Non-Communicable Diseases and also how to implementSMART in the Gandok community, Condongcatur, Depok, Sleman, Yogyakarta